PENGGUNAAN HONORIFIK SAPAAN DALAM ANIME OURAN KOUKOU HOSUTO KURABU KARYA BISCO HATORI - Nurhidayah Kusmawati; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2025)
Kusmawati, Nurhidayah, 2025. “The Use of Honorific in the Anime Ouran Koukou Hosuto Kurabu by Bisco Hatori.” Thesis. Padang: Japanese Language Education Program, Department of English Language and Literature, Faculty of Languages and Arts, Universitas Negeri Padang. Honorifics, as a form of respect towards the interlocutor, are crucial to use because employing polite and respectful address forms leads to positive responses in social relationships. This study aims to identify the various forms of honorifics and the factors influencing the use of honorifics in the anime Ouran Koukou Hosuto Kurabu episodes 1-12. The study uses a qualitative research method with a descriptive approach. The data for this research consists of speech events containing honorific address forms, and the data source is the anime Ouran Koukou Hosuto Kurabu by Bisco Hatori. Based on the data collection, the researcher found 61 instances of honorific address forms. These include: 1) personal names (24 data), 2) personal pronouns (5 data), 3) familial honorifics (7 data), 4) title honorifics (17 data), 5) job honorifics (5 data), and 6) professional honorifics (3 data). The influencing factors are, 1) situational context factors (14 data), 2) age factor (12 data), 3) gender factor (2 data), 4) social status factor (15 data), 5) kinship factor 10 data), 6) familiarity factor (8 data). Keywords: honorifics, anime, Ouran Koukou Hosuto Kurabu